The Impact of Reproductive Health Education on Delaying Early Marriage at Kartika IV-2 Jember High School - Dewi, Riskha Dora Candra; Sari, Dian Kartika (Indonesian Journal Publisher, 2025)
Early marriage is still a significant social problem in Indonesia, especially in areas with certain social and economic backgrounds. Jember Regency is one of the regions with a high rate of early marriage compared to the national average. This phenomenon is influenced by various factors, including family economic conditions, a culture that considers early marriage as normal, and a lack of education on reproductive health. The impact of early marriage is extensive, including reproductive health risks, psychosocial developmental disorders, limited access to education, and declining household economic conditions. Therefore, more effective prevention efforts are needed to reduce the number of early marriages, one of which is through reproductive health education in schools. This research used a qualitative method with a case study approach at SMA Kartika IV-2 Jember. Data were collected through in-depth interviews with 20 students who had received reproductive health education. In addition, observation and documentation were also conducted to strengthen the research findings. The data obtained were explained inductively to understand how reproductive health education contributes to delaying early marriage among students. The results showed that reproductive health education has a positive impact on increasing students' awareness of the risks of early marriage. Most students who have received education show a more choosy attitude in relationships and better understand the importance of physical and mental readiness before marriage. However, challenges remain, especially in dealing with social norms that still support early marriage. Therefore, synergy between schools, families, and the government is needed to strengthen reproductive health education and create policies that better support the prevention of early marriage.